Effect of single or dual inoculation of the arbuscular mycorrhizal fungus Glomus mosseae and root‑nodulating rhizobacteria on reproduction of the burrowing nematode Radopholus similis on non‑leguminous and leguminous banana intercrops - Veken, L. van der; Cabasan, M.T.N.; Elsen, A.; Swennen, Rony L.; Waele, D. de (Springer, 2021)
The bio-protective effect of either single or dual mycorrhizal (AMF) and rhizobial colonisation of the roots of non-leguminous and leguminous banana intercrops differing in host response to Radopholus similis on the reproduction of this important migratory endoparasitic nematode was examined. Included in the study were sorgho-Sudan grass (good R. similis host), sweet potato and common bean (intermediate hosts), soybean and sunn hemp (poor hosts), and marigold (non-host). Significant plant growth-promoting effect of single AMF and rhizobial colonisation in the good and intermediate R. similis hosts sorgho-Sudangrass (AMF) and common bean (AMF and rhizobium), respectively, was observed whereas this plant growth-promoting effect was absent in the other intercrops with the exception of sunn hemp with significant plant growth-promoting effect of AMF colonisation on fresh root weight. An additive plant growth-promoting effect of dual AMF and rhizobial colonisation (on fresh shoot weight) was only observed in the poor R. similis host soybean. Single AMF and rhizobial colonisation also resulted in a significant bio-protective effect against R. similis in sorgho-Sudangrass (AMF), sweet potato cv. Inzovu (AMF) and common bean (AMF and rhizobium). The growth-promoting and bio-protective effects of AMF colonisation were clearly present in the good and intermediate R. similis hosts with moderate to high relative mycorrhizal dependency (RMD) values ranging from 47% (sorgho-Sudangrass) to 65% (common bean) but absent in the intermediate R. similis host sweet potato, which had a negative RMD value, and in the poor and non- R. similis hosts. Overall, no suppressive effect of R. similis infection on AMF and rhizobial colonisation was observed except in soybean and sunn hemp in which AMF colonisation was significantly reduced.